Sailing dinghy hydrodynamic resistance by experimental and numerical assessments. (15th October 2020) - Begovic, E.; Bertorello, C.; Mancuso, A.; Saporito, A.
Abstract: Hull forms of high-performance sailing dinghies are very interesting for yacht designers. After a long period in which the attention has been focused on one-design boats, in recent years a few exciting restricted classes such as International Moth, International 14′, 18' Skiff and Class A catamaran become recognized in several countries and led to interesting advances in high-performance yacht design. "1001VELAcup R3" class is two people racing dinghy designed according to a box rule with limitation on LOA and Bmax and total sail area. The boats must be designed and built by students of European Universities and race yearly in Italy. This paper focuses on two best-ranked boats "LED" from the University of Palermo and "TryAgain" managed by the University of Naples but designed by the University of Roma3 team. These boats were definitely superior as regard motion resistance when tested without appendages during 2017 MIDWINTER INDOOR RACE and, although very different in main section shape, had comparable performances. The observed behaviours and the availability of experimental data suggested a suitable numerical approach and a fair comparison between experimental and numerical results is presented. Highlights: Resistance assessment of two 1001VELAcup R3 class sailing boats has been investigated by CFD and EFD. Experimental campaign on full scale boats has been performed at University of Naples Federico II during MIDWINTER indoor race. CFD resistance calculations starting from the measured trim and sinkage have been performed by University of Palermo. Obtained differences in resistance predictions are around 5%.